Socio‐Emotional Wealth Separation and Decision‐Making Quality in Family Firm TMTs: The Moderating Role of Psychological Safety. (12th May 2017) - Vandekerkhof, Pieter; Steijvers, Tensie; Hendriks, Walter; Voordeckers, Wim
ABSTRACT: Socio‐emotional wealth (SEW), defined as the firm's non‐financial aspects meeting the family's affective needs, has become the dominant paradigm in family firm research. Recent debate acknowledges potential SEW heterogeneity within family firms. This study considers the effect of polarizing opinions on SEW preservation among TMT members as a source of separation in the TMT. More concretely, we study the effect of SEW separation on TMT decision‐making quality, while taking into consideration behavioural integration as a team process and psychological safety as a team context. Based on a unique multiple respondent sample of 300 managers from 55 Belgian private family firms, we find that behavioural integration mediates the negative effect of SEW separation on TMT decision‐making quality. In addition, we find that the negative effect of SEW separation on behavioural integration is mitigated by psychological safety and even turns into a positive effect at high levels of psychological safety.